Political Landscapes : Forests, Conservation, and Community in Mexico - Boyer, Christopher R. (Christopher Robert) (Book collections on Project MUSE., 2015)
In this environmental history of twentieth-century Mexico, Christopher R. Boyer conceptualizes the forests of Chihuahua and Michoacán as political landscapes. Conflicts among local landowners, the federal government and timber companies politicized these geographies, demonstrating the crucial role that social forces play in the construction of environments.